ANALISIS PROVENANCE BATUPASIR FORMASI DOLOKAPA KABUPATEN GORONTALO UTARA BERDASARKAN DATA GEOKIMIA XRF - Sandi, I Nengah; Permana, Aang Panji; Kasim, Muhammad (EnviroScienteae, 2024)
The research location is located in Deme 1 Village, East Sumalata District, North Gorontalo Regency. The rock outcrops studied are sandstones which are part of the Dolokapa Formation which is spread in the northern part of the Tilamuta Sheet. This study aims to analyze the tectonic setting of the origin of the sandstones. The research method used to achieve the research objectives is using two methods consisting of field geological surveys and X-Ray Fluoresence (XRF) Geochemical laboratory analysis. Based on the results and discussion that the two sandstone samples are of the Fe-Shale and Fe-Sand types which originate from the ARC (oceanic island arc) tectonic setting.